Muslim Millennial Interest in Investing Sharia Shares - Muh. Irnandas; Muh. Noval Waliyuddinsyah (Prodi Ekonomi Syariah IAIN Sorong, 2024)
Investment decisions, financing decisions, and asset management decisions are the three key roles that investments play in financial management. Research on the capital market that looks at Muslim youth's interests and actions when investing in Islamic companies is still inadequate at this time. Since there hasn't been much research on intents in the Islamic capital market, it's important to recognise how interested and inclined Muslim youngsters are to engage in Islamic sham investing. Prior studies frequently focus on young people's impressions of investment instruments in general. This study tries to pinpoint and examine the elements that affect young Muslim investors' interest in purchasing Islamic stocks. This study's methodology is quantitative. The information used was gathered by the distribution of questionnaires to 100 participants. The SEM model is then the analytical technique utilised to determine the connection between the variables and the desire of millennial Muslims in investing in Islamic companies. The programme is SmartPLS 4. Validity, reliability, and the connection between variables x and y are the main topics of the analysis. The findings of this study suggest that millennial Muslims' interest in investing in sharia stocks is positively and significantly influenced by perceptions of sharia compliance, perceptions of investment goals, and perceptions of risk